High-Frequency Trading Strategies - Goldstein, Michael; Kwan, Amy; Philip, Richard (Management Science, 2023)
We examine the effect of high-frequency trading on market quality from the perspective of a limit order trader. By competing with slower limit order traders, high-frequency traders impose a welfare externality by selectively crowding out the most profitable limit orders. The order book imbalance immediately before each order submission, cancellation, and trade suggests that high-frequency traders strategically use limit order book information to supply liquidity on the thick side of the order book and demand liquidity from the thin side. This strategic behavior is more pronounced during volatile periods and when trading speeds increase. This paper was accepted by Bruno Biais, finance. Funding: This work was supported by the Centre for International Finance and Regulation [Grant T013]. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4539 .